Policy issues in informal market place and marketing system in Nepal: Experiences from the cities of Kathmandu Valley - Sharma, Puspa (Geographical Journal of Nepal, 2021)
Informal market places and marketing systems are important sectors in providing employment and income to the poor residents of Kathmandu Valley, the largest urban agglomeration of Nepal. The informal marketing system is a traditional system and has been operated in the valley since the long. This sector shows unique features in terms of marketing, spatial location, and transformation. In this paper, the salient features of the informal market places and marketing systems prevailing in the cities of Kathmandu valley are portrayed and based on these, five major policy issues are explored and suggested for consideration to the urban government for the better management of the informal market places and marketing systems.